Growth and Nonspecific Immunity Parameters of Rohu Fed with a Floating Feed Prepared from Locally Available Ingredients (CIFA-Carp Grower) - Das, krushna Chandra; Nayak, Ambika Prasad; Routray, Padmanav; Nayak, Santosh Kumar; Swain, Priyabrat; Mohanty, Snehalata (Indian Journal of Animal Nutrition, 2021)
A Grower feed carp (CIFA-Carp Grower) was formulated and prepared using locally available ingredients, minerals (with nano-selenium and nano-zinc) & vitamin mixture through extrusion technology and compared the performance with an existing feed used by farmers of eastern region. The developed feed contains 28 percent crude protein (CP) and 4 percent crude fat. The feed has been commercialized, IP protected and reached to aquaculture farmers covering about 10-12 states of India. As per the scheduled methodology of demonstration, rohu fingerlings (average 105 g) were stocked randomly into triplicate ponds for both control and treatment following a completely randomised design and stocking density of 7500/hectre was maintained for each pond. The fish of control ponds were fed with a mixture of groundnut oil cake (GNOC) and rice bran (50:50) with minerals & vitamins mixture where as fish of treatment ponds were fed with a grow out feed developed by ICAR-CIFA(CIFA-Carp Grower). During the experimental period of 10 months, growth, survivability, feed conversion ratio (FCR) and nonspecific immunity parameters of rohu fed with CIFA-Carp Grower were recorded and compared with rohu fed with an existing feed used by farmers of this region. The average size of fish after feeding with CIFA- Carp Grower were 1088 gm at 10 months of feeding with average feed conversion ratio (FCR) of 1.290 and it was higher than existing/traditional method of feeding. The results of the demonstration showed that weight gain, survivability, feed convetrsion ratio (FCR) and nonspecific immunity parameters of grow out rohu fed with CIFA-Carp Grower was higher compared to existing feed practiced by many farmers in this region. So, CIFA- Carp Grower may be popularised among farmers, entrepreneurs and researchers for aquaculture development of the whole country.